52.0k views
6 votes
Solve each system of equations using the elimination method

3x+4y=23
3x-2y=11

User Damp
by
5.2k points

1 Answer

8 votes

Answer: (x,y) = (5,2)

In other words, x = 5 and y = 2

====================================================

Step-by-step explanation:

Subtract the equations straight down.

  • The x terms subtract to 3x-3x = 0x and they go away (hence the term "elimination").
  • The y terms subtract to 4y-(-2y) = 6y
  • The right hand sides subtract to 23-11 = 12

We end up with 6y = 12 which solves to y = 2 after dividing both sides by 6.

Now use this y value to find x.

If we used the first equation, then we have these steps

3x+4y = 23

3x+4(2) = 23

3x+8 = 23

3x = 23-8

3x = 15

x = 15/3

x = 5

Or we could use the second equation

3x-2y = 11

3x-2(2) = 11

3x-4 = 11

3x = 11+4

3x = 15

x = 15/3

x = 5

We get the same x value either way.

The solution is (x,y) = (5,2)

To check the answer, plug those coordinates into each equation. After simplifying, you should get the same number on both sides.

------------------

Check:

3x+4y = 23

3(5)+4(2) = 23

15+8 = 23

23 = 23 .. that works

and,

3x-2y = 11

3(5)-2(2) = 11

15 - 4 = 11

11 = 11 .. that works as well

Both original equations are true for those x and y values.

The solution is fully confirmed.

User Fastobject
by
4.9k points